Penerapan Metode Jigsaw Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Akidah Akhlak - Ambo Bengnga,; Santi, Nursanti; Sumarni, Sumarni (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to analyze the application of the Jigsaw method to improve student learning outcomes in Akidah Akhlak learning in class IX B MTs As'adiyah Uloe. This type of research is a class action research (PTK) using a sequential design explanatory approach. The data collection methods used in this study are test, observation, and documentation methods. Data processing and analysis techniques using descriptive statistics by presenting data in the form of tables / graphs, calculating averages, and percentages using Ms. Excel. The research subjects in this study were class IX B students totaling 32 people with details of 13 men and 19 women. The results showed that the percentage of completeness of student learning outcomes in the pre-cycle was 41%, cycle I was 63%, and cycle II was 100%. The percentage of non-completion of student learning outcomes in the pre-cycle was 59%, cycle I was 37%, and cycle II was 0%.